Biological removal of gaseous sulfur dioxide through the reduction to hydrogen sulfide by means of Desulfovibrio desulfuricans. (January 2018) - Papi, S.; Montalvo, S.; Papic, Lj.; Borja, R.
Abstract: The biological removal of gaseous sulfur dioxide using the sulfate reducing bacteria Desulfovibrio desulfuricans is studied. Laboratory-scale bioreactors were designed to generate sulfur dioxide in them through a chemical reaction. To evaluate the biological reduction, three kinetics (in triplicate) were taken in batch mode with loads of 15, 20 and 25 mmol of SO2 generated in the gas phase per liter of culture medium in the liquid phase. Lactate was used as substrate (electron donor) and carbon source. The experimental results showed a 100% SO2 reduction for all the evaluated loads. The tests lasted 24, 72 and 192 h, with lower, intermediate and higher loads, respectively. The total sulfide (S 2− ) produced varied between 75 and 126 mg for the tests with lower and higher load, respectively. These amounts were composed of a fraction in the aqueous phase (287 and 533 mg of S 2− /L) and another in the gas phase (0.9 × 10 8 and 2.7 × 10 8  μg H2 S/m 3 ). The mass ratio between product formation (sulfide) and electron donor consumption (expressed as COD) ranged from 81% to 90% of the theoretical value (0.67 mg of sulfide produced per mg of COD consumed). Graphical abstract: Highlights: Biological SO2 removal with Desulfovibrio desulfuricans was studied. Lactate was used as substrate (electron donor) and carbon source. Loads of 15, 20 and 25 m-moles of gaseous SO2 per liter of culture medium were tested. 100% SO2 reduction were observed after 24 and 192 h for the lower and higher load. Ratio between sulfide formation and COD reduction ranged from 81 to 90% of theoretical value.